Why Norway has more female local councillors than Denmark: a crack in the Nordic gender equality model?. Issue 2 (20th October 2022) - Segaard, Signe Bock; Kjaer, Ulrik; Saglie, Jo
Abstract: The article explores why women are better represented in municipal councils in Norway than in Denmark. This comparative case study offers a most similar systems design, as these two countries are similar on most relevant institutional variables, such as local government systems, electoral systems, party systems and societal gender equality, but they deviate on the dependent variable of women's representation. Two unique comparative data sets are analysed: representative voter surveys and register data on all candidates (from the 2019 Norwegian and 2017 Danish municipal elections). The study focuses on demand-side explanations and concludes that institutional explanations do not appear relevant. Instead, the parties' candidate selection matters: Norwegian parties are more concerned with gender balance than their Danish counterparts. Finally, the article discusses why this is the case and asks whether gender equality plays a more prominent role on the societal agenda in Norway than in Denmark.